NATO in search of a vision - Aybet, Gülnur; Moore, Rebecca R. (Georgetown University Press, 2010)
This volume brings together scholars and policy experts from both sides of the Atlantic to examine the key issues that NATO must address in formulating a new strategic vision. With thoughtful and reasoned analysis, it offers both an assessment of NATO's recent evolution and an analysis of where the Alliance must go if it is to remain relevant in the twenty-first century.